Additional Charges in Sales Transactions via QRIS: A Sharia Economic Law Perspective at Aini Cake Shop - Sagita Auranti; Anggi Irawan; Musthofa, Ahmad Misbakh Zainul (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
The Quick Response Code Indonesian Standard (QRIS) is a QR code-based payment system that integrates various codes from different payment service providers, enabling micro, small, and medium enterprises (MSMEs) to conduct transactions using a single code. This study aims to analyze the practice of adding fees to sales transactions using QRIS from the perspectives of Indonesian Positive Law and Sharia Economic Law. The research employs a qualitative method with a literature review approach, drawing on books, journals, scholarly works, and other relevant sources. The analysis examines the concept of ijarah as a contract for the use of services—either as rent for the benefit of goods or wages for labor—and the legal provisions for additional charges in non-cash transactions. The findings indicate that, from the perspective of Sharia Economic Law, additional fees are permissible if they meet the principles of fairness, transparency, and compliance with Sharia, as service providers are entitled to compensation for the services rendered. Meanwhile, under Indonesian Positive Law, such practices must adhere to consumer protection regulations and cost transparency requirements. Therefore, additional fees in QRIS transactions can be deemed acceptable as long as they comply with the legal principles of both systems.